1994
DOI: 10.1164/ajrccm.149.2.8306030
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of asthma and atopy in two areas of West and East Germany.

Abstract: The German reunification offers a unique opportunity to study the impact of environmental factors on the development of childhood respiratory and allergic disorders in ethnically similar populations. We investigated the prevalence of asthma, hay fever, atopy, and bronchial hyperresponsiveness (BHR) in 9- to 11-year old children in West Germany (n = 5,030) and East Germany (n = 2,623). A self-administered questionnaire was distributed to the parents. Children underwent cold air challenge and allergy skin prick … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

39
429
7
36

Year Published

1998
1998
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 817 publications
(511 citation statements)
references
References 20 publications
39
429
7
36
Order By: Relevance
“…La prevalencia de asma y rinitis alérgica ha presentado un aumento progresivo en los últimos años, lo que se ha atribuido a diversos factores relacionados con el estilo de vida occidental como cambios en la dieta, mayor permanencia en espacios cerrados, exposición a ciertos alergenos y mejor nivel socioeconómico [11][12][13][14][15][16][17][18][19] .…”
Section: N V E S T I G a C I ó N A R T í C U L O D E I N V E S T I unclassified
“…La prevalencia de asma y rinitis alérgica ha presentado un aumento progresivo en los últimos años, lo que se ha atribuido a diversos factores relacionados con el estilo de vida occidental como cambios en la dieta, mayor permanencia en espacios cerrados, exposición a ciertos alergenos y mejor nivel socioeconómico [11][12][13][14][15][16][17][18][19] .…”
Section: N V E S T I G a C I ó N A R T í C U L O D E I N V E S T I unclassified
“…Another line of compelling evidence of the East-West gradient in the occurrence of atopic diseases comes from studies performed in Germany after the reunification in 1989. von Mutius et al (10) showed that in genetically similar individuals, the prevalence of atopic diseases [current asthma, bronchial hyperresponsiveness, atopic sensitization assessed by skin prick tests (SPT)] were significantly higher among school children (n ¼ 7445) living in the former West (Munich) as compared with the children (n ¼ 4534) in former East Germany (Leipzig and Halle). This study confirmed the preliminary findings published 2 years earlier by the same group (11).…”
mentioning
confidence: 99%
“…Epidemiological and clinical studies have provided intriguing data that suggest that a link exists between the relative lack of infectious diseases and the increase in allergic disorders (9,56,57); this is referred to as the "hygiene hypothesis." According to this hypothesis, viral and bacterial infections prevent the induction of allergen-specific Th2 cells because they establish Th1-biased immunity.…”
mentioning
confidence: 99%